A longitudinal examination of the relationship between cannabis use and cognitive function in mid-life adults - McKetin, Rebecca; Parasu, P.; Cherbuin, N.; Eramudugolla, R.; Anstey, K. (Elsevier Ireland Ltd, 2016)
Background: The relationship between cannabis use and cognitive function in mid-life has rarely been examined despite verbal learning deficits in young adults. Method: A longitudinal cohort study of 1,897 Australians recruited at 40–46 years of age and followed up 4 years (94%) and 8 years (87%) later. Random effects regression was used to assess within- and between-person associations between cannabis use and cognitive function across waves of data, and examine whether age-related changes in cognitive performance were modified by cannabis use. The first list of the California Verbal Learning Test (immediate and delayed recall), Symbol Digit Modality Test, Digit Backwards, simple and choice reaction time tasks, were administered at each wave. The Spot-the-Word test was used to assess premorbid verbal ability. Self-reported cannabis use in the past year (no use, < weekly use, ≥ weekly use) was assessed at each wave. Findings: Participants who used cannabis ≥ weekly had worse immediate recall (b = −0.68, p = 0.014) and showed a trend toward worse delayed recall (b = −0.55, p = 0.062) compared to non-users after adjusting for correlates of cannabis use and premorbid verbal ability. These effects were due to between-person differences. There were no significant within-person associations between cannabis use and recall, nor was there evidence of greater cognitive decline in cannabis users with age. Conclusions: Mid-life cannabis users had poorer verbal recall than non-users, but this was not related to their current level of cannabis use, and cannabis use was not associated with accelerated cognitive decline.